Anaesthesiology in China: A cross-sectional survey of the current status of anaesthesiology departments - Changsheng Zhang, MD, PhD; Shengshu Wang, MD, PhD; Hange Li, MD; Fan Su, MD, PhD; Yuguang Huang, MD; Weidong Mi, MD, PhD (Elsevier, 2021)
Background: The discipline of anaesthesiology in China has undergone historical changes and development during the past century. However, nationwide comprehensive data on the current status of each hospital department providing anaesthesia care has been lacking since the discipline was first established in China. This information is essential for effective regulation of healthcare policies by both the professional associations and the government health ministry. Therefore, a nationwide survey was set up in 2018 to investigate the current status of Chinese anaesthesiology. This paper reports the findings of the survey. Methods: We performed a cross-sectional nationwide census survey of the current status of each hospital department providing anaesthesia care in 31 provinces across the Chinese mainland. The content of the survey included general information of the department, the hospital level and scale, the volume of the anaesthesiology department, the characteristics of anaesthesiologists, and the caseload of the anaesthesiology departments. Face-to-face interviews were performed by trained interviewers. The Chinese Anaesthesiology Department Tracking Database (CADTD) was established during the survey. Data quality control was undertaken by the investigation committee throughout the survey process. Findings: The nationwide census survey was completed by 11,432 hospital departments providing anaesthesia care throughout mainland China from June 1, 2018 to June 30, 2019. Among the 11,432 departments, 4591 (40•16%) belonged to specialised hospitals, while 6841 (59•84%) were affiliated to general hospitals. The proportion of independent anaesthesiology departments was 45•15% in mainland China. There was a total of 92,726 anaesthesiologists, or 6•7 per 100,000 of the population. Regions with better economic conditions had more anaesthesiologists per 100,000 of the population. From 2015 to 2017, the workload of anaesthesiologists has increased by 10%. Interpretation: The discipline of anaesthesiology in China has entered a rapid development phase. However, the current status of anaesthesiology is not well defined, which makes it difficult to meet the needs of the increasing Chinese healthcare demand. The evidence from this survey offers valuable information for policy makers and anaesthesiology associations to monitor the development of the discipline and regulate healthcare policies effectively.